Ethnomedicinal Plants Used by the Pnar Tribes of Meghalaya for the Treat-ment of Diabetes Mellitus: Ethnomedicinal Plants Used by the Pnar Tribes of Meghalaya for the Treatment of Diabetes Mellitus - Bamon, Fedalia; Lalnundanga (Journal of Tropical Life Science, 2023)
Diabetes mellitus is the world’s major public health issue and has been dubbed the “Silent Epidemic” of the twenty-first century. This is the first ethnobotanical exploration to document the folk medicinal usage of plants with therapeutic antidiabetic properties by the Pnar tribes of East Jaintia Hills, Meghalaya. Forty-one practitioners and knowledgeable people were interviewed using a semi-structured questionnaire. Field inventories were then conducted to collect plant material for botanical identification. In this study, 51 plant species belonging to 34 families and 45 genera have been identified. This study indicates that herbs were the most prevalent living form used (N = 23) for the treatment. Rhus semialata is one of the most frequently cited medicinal plants, with a Relative Frequency of Citation (RFC) of 0.73. Moreover, the details about the phytochemicals and the pharmacological activities of identified plant species have been reviewed and disclosed. Agricultural expansion, deforestation, urbanization, and unscientific exploitation of the forests were cited most when respondents were asked about the threat to medicinal plants. Of the 51 plant species, 12 are included on the IUCN Red List. Therefore, this documentation of indigenous plants would create awareness about the importance of medicinal plants and their conservation and protection.